Peasant markets, ¿a strategy to implement food sovereignty? Case Sibate (Cundinamarca) - Pachón-Romero, Jenny Paola; Pachón-Ariza, Fabio Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Peasant markets have been a market strategy implemented in several regions of Colombia looking for bringing closer the producer to the consumer and to promote the political engagement of the peasantry. The current research analyzes the process of peasant markets through a case study in Sibate (Cundinamarca)-Colombia based on the logic of the food sovereignty principles. To this end, a mixed methodology was used with interviews and surveys of farmers, consumers and public officials participating in the strategy. The results emphasize that just two of the food sovereignty principles, food alternative markets and social peace, have been carried partially through. In this sense, food production for local consumption, the reduction of middleman participation, solidarity and support among actors, were remarked as the most critical aspects put into practice. However, the application of other features of food sovereignty is just emerging. Presumably, this is because of the weak democratic control carried out for the stakeholders, or because the peasant market in Sibate has mainly an economic focus given to the strategy.